The Representation of Headache and Pain Through the Lens of Cultural Neuroscience - Riyanto Sofyan, Henry; Hasan, Sandy (Departemen Neurologi Fakultas Kedokteran Universitas Indonesia, 2026)
Background: Headache is a universally experienced neurological condition; however, its representation and subjective interpretation vary considerably across cultural contexts. Cultural neuroscience provides an integrative framework for understanding how sociocultural influences shape headache and pain experiences through identifiable neural mechanisms. Objective: This narrative review synthesizes empirical and epidemiological evidence regarding cross-cultural variations in headache presentation, psychophysical pain profiles, and systemic clinical management barriers across diverse global populations. Methods: A structured literature search was conducted across the PubMed and ScienceDirect databases to identify peer-reviewed studies published between 2016 and 2026 focusing on cultural neuroscience, primary headache disorders, and cross-cultural pain perception. A total of 20 articles meeting eligibility criteria were selected for qualitative narrative synthesis. Results: Cross-cultural differences in headache expression are heavily driven by lived experiences of socioenvironmental stress and structural inequities. Chronic exposure to systemic discrimination, lower socioeconomic status, and acculturation stress function as physical stressors that accelerate central sensitization and the chronification of episodic headaches. Furthermore, culturally distinct illness models and expectations of clinical stoicism significantly influence symptom communication, contributing to diagnostic misclassification. Finally, structural healthcare barriers perpetuate profound inequities in patient access to novel, targeted migraine therapies. Conclusion: Nociceptive processing appears to be relatively consistent across populations, whereas cultural factors influence the affective and contextual modulation of headache through identifiable neural circuits. Clinical implications highlight the importance of culturally informed assessment strategies and personalized therapeutic interventions.